A Novel ShK-Like Toxic Peptide from the Transcriptome of the Cnidarian Palythoa caribaeorum Displays Neuroprotection and Cardioprotection in Zebrafish - Qiwen Liao; Guiyi Gong; Shirley Weng In Siu; Clarence Tsun Ting Wong; Huidong Yu; Yu Chung Tse; Gandhi Rádis-Baptista; Simon Ming-Yuen Lee (Toxins, 2018)
Palythoa caribaeorum (class Anthozoa) is a zoantharian which, together with other cnidarians, like jellyfishes, hydra, and sea anemones, possesses specialized structures in its tissues, the cnidocytes, which deliver an array of toxins in order to capture prey and deter predators. The whole transcriptome of P. caribaeroum was deep sequenced, and a diversity of toxin-related peptide sequences were identified, and some retrieved for functional analysis. In this work, a peptide precursor containing a ShK domain, named PcShK3, was analyzed by means of computational processing, comprising structural phylogenetic analysis, model prediction, and dynamics simulation of peptide-receptor interaction. The combined data indicated that PcShK3 is a distinct peptide which is homologous to a cluster of peptides belonging to the ShK toxin family. In vivo, PcShK3 distributed across the vitelline membrane and accumulated in the yolk sac stripe of zebrafish larvae. Notably, it displayed a significant cardio-protective effect in zebrafish in concentrations inferior to the IC50 (<43.53 ± 6.45 µM), while in high concentrations (>IC50), it accumulated in the blood and caused pericardial edema, being cardiotoxic to zebrafish larvae. Remarkably, PcShK3 suppressed the 6-OHDA-induced neurotoxicity on the locomotive behavior of zebrafish. The present results indicated that PcShK3 is a novel member of ShK toxin family, and has the intrinsic ability to induce neuro- and cardio-protective effects or cause cardiac toxicity, according to its effective concentration.